Analysis of Radiation Exposure Dose according to Location Change during Radiation Irradiation - 조창호; 김정래 (International Journal of Advanced Culture Technology(IJACT), 2024)
During an X-ray examination, the beam of radiation is dispersed in many directions. We believe that managing radiation dose is about providing transparency to users and patients in the accurate investigation and analysis of radiation dose. The purpose of measuring the radiation dose as a function of location is to ensure that medical personnel using the equipment or participating in the operating room are minimally harmed by the different radiation doses depending on their location. Four mobile diagnostic X-ray units were used to analyze the radiation dose depending on the spatial location. The image intensifier and the flat panel detector type that receives the image analyzed the dose by angle to measure the distribution of the exposure dose by location. The radiation equipment used was composed of four units, and measuring devices were installed according to the location. The X-ray (C-arm) was measured by varying the position from 0 to 360 degrees, and the highest dose was measured at the center position based on the abdominal position, and the highest dose was measured at the 90° position for the head position when using the image intensifier equipment. The operator or medical staff can see that the radiation dose varies depending on the position of the diagnostic radiation generator. In the image intensifier and flat panel detector type that accepts images, the dose by angle was analyzed for the distribution of exposed dose by position, and the measurement method should be changed according to the provision of dose information that is different from the dose output from the equipment according to the position.